Rancang Bangun Grinding Attachment Untuk Proses Pengerindaan Silindris Permukaan Luar Pada Mesin Bubut - Handika Furqon; Pranowo Sidi; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
To produce commercial products must meet certain criteria or standards. Therefore, the facilities and infrastructure in the PPNS workshop are required to be able to work on products that meet standards. One example of standard workmanship is roughness. Some products are required to have a small roughness value. However, when working on a workpiece on a conventional lathe, the roughness value is still relatively large. To achieve the least roughness required further work on the grinding machine. Therefore a grinding attachment tool is needed that can be installed on a lathe without switching to a grinding machine and can produce a small roughness value. In this study using the Ulrich method. Based on the identification of needs, several concept designs were made then the best concept was selected by considering 5 aspects including function, geometry, fabrication, maintenance, and cost. The best concept chosen is concept 3. Design using Autodesk Fusion 360 and AutoCAD software. then carried out fabrication and testing. In testing this tool produces an average roughness value of 1.627 µm or N7. The total cost of making is around 2 million.